E-module ABRA-Maths - early mathematics learning via mini tennis / Rahela Abdul Rahim ... [et al.] - Abdul Rahim, Rahela; Ibrahim, Haslinda; Baharom, Fauziah; Abdul Rahim, Mohd. Rahizam; Morazuki, Syahrul Ridhwan (2021)
Since play activities in the teaching and learning process in school can benefit children in terms of development, learning and motivation as well as fun to play, the researchers plan to introduce the technique of learning basic mathematics for children through a mini tennis game called ABRA-Maths .This technique can be a guide and guidance to instructors who will teach the basics of maths to children through tennis game practice. To ensure that ABRA-Maths learning techniques can be mastered among teachers through school activities, a systematic learning method is introduced. ABRA-Maths e-module is a digitally developed basic mathematics learning module aimed at helping teachers master basic mathematics teaching methods through tennis mini-games. The proposed e-module contains instructions and videos showing how the training process or activity should be carried out.